Relationship Between the Frequency of Reading English Texts and Students’ English-Speaking Skills - Fitri Suryani; Nia Liska Saputri (HANA: Humanities and Academic Narratives in Education, 2026)
Despite years of formal English instruction, many Indonesian senior high school students remain reluctant and unable to speak English fluently, largely due to limited exposure to authentic language input outside the classroom. Although reading is a readily accessible source of such input, its specific contribution to speaking performance has rarely been examined empirically at the senior high school level in Indonesia, leaving a gap in understanding how reading frequency in particular relates to oral proficiency. This study investigated the relationship between the frequency of reading English texts and students' English speaking skills at An Nur Aliyyah Senior High School, using a quantitative correlational design. The sample consisted of 30 eleventh-grade students selected through purposive sampling from a population of 76. Reading frequency was measured using a 30-item Likert-scale questionnaire, while speaking skills were assessed through an oral test covering pronunciation, intonation, accuracy, comprehension, and fluency. Data were analyzed using descriptive statistics, Pearson Product-Moment correlation, and t-test analysis. Results showed a positive and significant correlation between reading frequency (M = 66.00) and speaking skills (M = 77.66), with reading frequency accounting for 64.7% of the variance in speaking performance (t = 7.16 > 1.70, p < 0.05). These findings suggest that integrating reading activities into English instruction can support the development of students' speaking proficiency.